Involvement of theenvironmental relevanceof groundwaterin ruralmunicipality ofGado Bravo-PB - Aguiar, Sara Camêlo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work to study area rural of the municipality of Gado Bravo, located in the middle region of the Paraíba arid and its purpose was to analyze, according to the perception of the families, the commitment of the environmental relevance of groundwater in rural Gado Bravo, focusing on the contamination and the finiteness of the resource. It was used a qualitative approach and adopted a survey of the exploratory type, an open interview was applied to 83 families, representing about 5% of the universe consists of 1,661 families. According to the results, despite the important role that groundwater plays in the daily lives of families in rural areas of Gado Bravo revealed that their environmental relevance is compromised in part due to the prevailing ignorance of these families about the possibility of contamination and finiteness of the resource.